Investigation of tacit knowledge measurement methods - Rashid A.M.; Bin Hassan Z.; Al-Oqaily A.T. (Asian Research Publishing Network, 2023)
The knowledge management services are important to provide competitive advantages for institutions of higher learning organizations. However most organizations are facing challenges to manage and to develop the tacit knowledge that to support services and products quality due to weaknesses of knowledge measurement processes. The main objective of this study is to investigate the roles of knowledge and effectively knowledge measurement factors in the university environment. The quantitative data collected using questionnaire from Tenaga Nasional (UNITEN) in Malaysia as a case study was analyzed finding tacit knowledge measurement factors. The significant results show that the knowledge measurement factors are not applied efficiently, thus the opportunity to use the available tacit knowledge resources for best knowledge implementations would be missed. 2005 - 2015 JATIT & LLS. All rights reserved.